ANTESEDEN DARI KESETIAAN MEREK - Iin Triyani; Robert Kristaung (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2014)
Purpose of this research is to analyze the effects of service quality, price, purchase decision,perceived quality, design, and store environment on brand loyalty at Beauty Salon in JakartaTheoretical model that used in this study is the hypothetical testing method, that means toexamine is there the direct effect of service quality, price, purchase decision, perceived quality,design, and store environment on brand loyalty at Beauty Salon in Jakarta using the MultipleRegressions and ANOVA One Way Method.Result of this study states that: (1) There is the positive influence of service quality on brandloyalty; (2) There is the positive influence of price on brand loyalty;(3) There is the positive influence of purchase decision on brand loyalty; (4) There is the positiveinfluence of perceived quality on brand loyalty; (5)There is the positive influence of design onbrand loyalty; (6) There is the positive influence of salon environment on brand loyalty; and(7)There is difference of brand loyalty between mall beauty salon, housing beauty salon, andsettlement beauty salon.Managerial implications of this study is that management must consider many factors that caninfluence service quality, price, purchase decision, perceived quality, design, and salon storeenvironment on brand loyalty at beauty salon in Jakarta in efforts to build and enhance thebrand loyalty.Keywords : Service quality, price, purchase decision, perceived quality ,design, SaloonEnvironment, Brand Loyalty, Beauty Salon.